5‐HT2B Receptor Antagonists Reduce Nerve Injury‐Induced Tactile Allodynia and Expression of 5‐HT2B Receptors. Issue 1 (25th January 2015) - Pineda‐Farias, Jorge B.; Velázquez‐Lagunas, Isabel; Barragán‐Iglesias, Paulino; Cervantes‐Durán, Claudia; Granados‐Soto, Vinicio
ABSTRACT <table-wrap position="anchor" orientation="portrait"> Preclinical Research </table-wrap> This work was performed to assess the effects of intrathecal serotonin 2B (5‐HT2B) receptor antagonists in rats with neuropathic pain. With RS‐127445, its effect was also determined on 5‐HT2B receptor expression. Neuropathic pain was induced by L5/L6 spinal nerve ligation. Western blotting was used to determine 5‐HT2B receptor expression. Dose‐response curves with the 5‐HT2B receptor antagonists 2‐amino‐4‐(4‐fluoronaphth‐1‐yl)‐6‐isopropylpyridine (RS‐127445, 1–100 nmol) and 1‐[(2‐chloro‐3, 4‐dimethoxyphenyl)methyl]‐2, 3, 4, 9‐tetrahydro‐6‐methyl‐1H‐pyrido[3, 4‐b]indole hydrochloride (LY‐266097, 1–100 nmol) were performed in rats. Tactile allodynia of the left hind paw (ipsilateral) was assessed for 8 h after compound administration. Intrathecal injection of the 5‐HT2B receptor antagonists RS‐127445 and LY‐266097 diminished spinal nerve ligation‐induced allodynia. In contrast, intrathecal injection of the 5‐HT2 receptor agonist (±)‐2, 5‐dimethoxy‐4‐iodoamphetamine hydrochloride (DOI, 10 nmol) did not modify tactile allodynia induced by nerve ligation. L5/L6 nerve ligation increased expression of the 5‐HT2B receptors in the ipsilateral, but not contralateral, dorsal root ganglia. Furthermore, nerve injury also enhanced 5‐HT2B receptor expression in the ipsilateral dorsal part of the spinal cord. Intrathecal treatment with RS‐127445 (100 nmol) diminished spinal nerve injury‐induced increased expression of 5‐HT2B receptors in dorsal root ganglia and spinal cord. Our results imply that spinal 5‐HT2B receptors are present on sites related to nociception and participate in neuropathic pain. © 2014 Wiley Periodicals, Inc Drug Dev Res 76 : 31–39, 2015